"Quem ensinará aos cristãos a serem cristãos?": uma abordagem fenomenológica na compreensão da homofobia religiosa - Silva, Laionel Vieira da (2019)
Discrimination against homosexuals is constructed by various social devices that tend to naturalize heterosexuality as the only legitimate possibility of expression of human sexuality. This supposed naturalness is propagated discursively as true in our society, based on aspects of some hegemonic theological traditions and tries to define bodies and desires, closely linked to a masculine and feminine binary that holds an explanation of the worldview that is exclusive to those who deviate from standard. In this context of exclusion, religious homophobia appears as a discourse of prejudice based on a religious worldview. This study is a phenomenological field research on the phenomenon of religious homophobia, developed through interviews with ten students of the Religious Sciences course of the Federal University of Paraíba. The central objective is to understand the meanings of religious homophobia by these students. From this study it was possible to understand some factors that contribute to the propagation of religious homophobia, such as religious intolerance; and factors that combat religious homophobia such as studies about diversity in the religious field. With this work it is possible to observe the role of the Sciences of Religions in the formation of students, as a Science capable of favoring contact with the expressions of human diversity.